2022
DOI: 10.25259/apos_37_2021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clear aligners in producing molar distalization: Systematic review

Abstract: Objectives: The aim of this review is to systematically analyze the efficacy of molar distalization using clear aligners in non-growing Class II patients. Materials and Methods: A complete search across the electronic database through PubMed, Cochrane, Google scholar, LILACS, and manual search of orthodontic journals were done till 2019. Studies were selected on the basis of PRISMA guidelines. Results: A total of four articles were included in this review. The amount of molar distalization reported was 2–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Regarding the CAT efficacy in achieving the distalization movement, our results agreed with those of previous studies [1,17,18,24,34,40,41], showing a significant improvement in the sagittal position of first molars, with an average distalization movement of 2.5 mm.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the CAT efficacy in achieving the distalization movement, our results agreed with those of previous studies [1,17,18,24,34,40,41], showing a significant improvement in the sagittal position of first molars, with an average distalization movement of 2.5 mm.…”
Section: Discussionsupporting
confidence: 91%
“…According to the other studies presented in the literature [1,17,18,24,34,40,41], also in our research, no statistically significant movements were detected at the premolar level. Slight differences were found at the level of the second premolars, attributable to the start of distal movements, as required by the protocol, but nonetheless not significant.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Even though treatment with a clear aligner is shorter than that with braces, some studies have indicated that the clear aligner may not provide enough occlusion contacts, torque control, and retention [11]. In addition, Verma and George reported the duration of sequential molar distalization with aligners to be excessively long (21 ± 3 months) [12]. The clear aligners can be combined with various types of auxiliaries prior to aligner treatment, such as the Carriere ® Motion 3D (CM3D) by Henry Schein Orthodontics ® (Carlsbad, CA, USA) appliance, to enhance the correction forces [13] and minimize the occupation of the oral cavity, which improves patient comfort and speech compared with conventional appliances such as braces [14].…”
Section: Introductionmentioning
confidence: 99%